2014
DOI: 10.3329/bjvm.v12i2.21263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Medicinal Plants on Haematology and Serum Biochemical Parameters of Village Chickens Naturally Infected with <i>Heterakis gallinarum</i>

Abstract: The effects of Aloe ferox, Agave sisalana and Gunnera perpensa on haematological and biochemical parameters of village chickens naturally infected with Heterakis gallinarum were evaluated. One hundred and twelve mature village chickens were randomly allotted into 14 groups of 8 chickens. Group 1 and 2 were orally administered 1 mL distilled water for 4 consecutive days and 1 mL mebendazole (once), respectively. Groups 3-6 received 1 mL orally of aqueous leaf extract of A. ferox for 4 consecutive days, groups 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Mwale et al [70] evaluated the haematological and serum biochemical parameters of G. perpensa aqueous leaf extract in village chickens naturally infected with Heterakis gallinarum . From day 0 to 14, haematocrit was reduced for chickens orally administered with G. perpensa 50, 100, and 400 mg/kg doses and haemoglobin was out of the range on day 0 and improved to be within the range on days 7 and 14.…”
Section: Anthelminticmentioning
confidence: 99%
“…Mwale et al [70] evaluated the haematological and serum biochemical parameters of G. perpensa aqueous leaf extract in village chickens naturally infected with Heterakis gallinarum . From day 0 to 14, haematocrit was reduced for chickens orally administered with G. perpensa 50, 100, and 400 mg/kg doses and haemoglobin was out of the range on day 0 and improved to be within the range on days 7 and 14.…”
Section: Anthelminticmentioning
confidence: 99%
“…Such medicinal plants include, Aloe ferox V (Mwale et al, 2014), Telfaria occidentalis (Dada and Abiodun, 2014) and Moringa oleifera (Ojo et al, 2015). The effects of any feed ingredient including medicinal plants on the haematological factors of the livestock are of immense assistance in deciding whether or not such a feed ingredient will be safe as feedstuff (Mitruka and , 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The significant effect on red blood cell differentials indicated that the extract affected the process of erythropoiesis probably by the phytochemicals interfering with the secretion and/or activity of erythropoietin ( Awe and Banjoko, 2013 ; Mugisha et al, 2014 ; Zaruwa et al, 2016 ). Diminished levels of mean platelet volume and procalcitonin could probably be due to presence of toxic phytochemicals that interfere with the functioning of thrombopoietin or cause inflammation of the bowel ( Mwale et al, 2014 ). The significant lowering of the pH indicated the potential of the extract to cause acidosis probably by stimulating the secretion of hydrogen ions into blood and/or inhibiting their renal excretion.…”
Section: Discussionmentioning
confidence: 99%